The Importance of Stem Borer, Apomecyna saltator Fabricius (Coleoptera: Cerambycidae) in Honey Pumpkin Plants (Cucurbita moschata Dusch) - Wilyus Wilyus; Fheny Rama Shen Thaury; Novalina Novalina (Journal of Applied Agricultural Science and Technology, 2023)
Currently, honey pumpkin plants are widely looked at and are in great demand for cultivation. Honey pumpkin production is in great demand with a relatively high price and can be stored for a relatively long time. Apomecyna saltator Fabricius (Coleoptera: Cerambycidae) as a pest of honey pumpkin in Indonesia is something that has been just known. The study about A. saltator on honey pumpkin is limited.  This research was conducted to determine: the relationship between honey pumpkin plant phenology and investment of A. saltator; the effect of A. saltator infested to plant age, the length of productive period and production of honey pumpkin plants; and the importance of A. saltator on honey pumpkin plants. The study was designed with 2 treatments, namely A (honey pumpkin plants that were left exposed to A. saltator obtained by planting honey pumpkins in areas endemic to A. saltator) and B (honey pumpkin plants that were not attacked by A. saltator obtained by wrapping the honey pumpkin plant stems using plastic wrap from the base of the stem which was applied from 7 days after planting and continued every day in line with plant growth until the wrapped stems were 1.5 m long). The treatments were in five replications. Observation variables include; plant phenology, symptoms of A. saltator attack, age, length of productive period, and production of honey pumpkin plants. The research shows that A. saltator investment in honey pumpkin plants occurs from the vegetative phase when the plant is 2-3 weeks old until the final generative phase (fruit ripening). The attack of A. saltator had a significant effect on reducing age, length of productive period and production of honey pumpkin plants. Based on the pest economic meaning, A. saltator is classified as an important pest of honey pumpkin plants.